Verification of H5 and IL-15 gene expressions from H5-recombinant fowlpox viruses coexpressing host cytokine by using sds-page and western blotting - Zulkifli, Nurul Farhana (2015)
A development of effective vaccine as a treatment against avian influenza virus (AIV) has been introduced since the 1980s by using inactivated vaccines. A recombinant fowlpox virus expressing AIV haemagglutinin H5 gene, co-expressed with chicken interleukin (IL)-15 cytokine has been constructed previously. In this study, the recombinant fowlpox virus (rFWPV) were analysed by using SDS-PAGE and Western blotting to verify the expression of H5 and IL-15 genes. The protein samples were separated by SDS-PAGE and transferred onto the surface of nitrocellulose membrane electrophoretically, by semi-dry Western blotting technique. Mouse β-actin, anti-IL-15, ab62587, and ab21292 primary antibodies were used to probe the membrane after blocking process. The antibody-antigen complexes were conjugated with alkaline phosphatase coupled to a secondary anti-IgG antibody which were either anti-mouse, anti-goat, or anti-rabbit, depending on the specific primary antibodies. The membranes were then developed by using commercially available WesternBreeze® Chromogenic Immunodetection System. Early findings revealed that false positive expressions were detected in all of the gel wells including negative controls, based on the presence of non-specific bands of 56 kD and 42 kD. Later results showed a 42 kD protein band size for β-actin expression, however the expressions of H5 and IL-15 proteins in the rFWPV were unsuccessful.